Some new species of Corynespora - and SANJAY K. SINGH, MEENU, ARCHANA SINGH (Indian Phytopathology, 2002)
Descriptions and illustrations of C. alstoniae sp.nov. and C. woodfordiana sp.nov. on Alstonia scholaris and Woodfordia fruticosa, respectively, in Nepal, and C. euphorbiacearum sp.nov. on cassava in Uttar Pradesh, India, are presented.